2004
DOI: 10.1016/j.femsle.2004.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression during interactions betweenHeterobasidion annosumandPhysisporinus sanguinolentus

Abstract: Using mRNA differential display we have identified differentially expressed genes in non-self-interacting vs. single mycelia of the conifer pathogen Heterobasidion annosum and the wood decomposing basidiomycete Physisporinus sanguinolentus. Altogether 39 differentially displayed bands were cloned and sequenced, corresponding to 21 unique genes, which were confirmed by semi-quantitative RT-PCR to be differentially expressed. Further confirmation of differential gene expression was made by real time RT-PCR. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 23 publications
0
30
0
2
Order By: Relevance
“…In the case of the interaction between P. coccineus and C. puteana, our data are convergent with these findings (609 overexpressed and 734 underexpressed), but for the interaction with B. cinerea, our results are divergent, with the number of underexpressed transcripts almost 7 times higher than the number of overexpressed transcripts. Multiple studies have reported that interspecific fungal interactions lead to genetic repression (11,(26)(27)(28), but the cause of this regulation is unclear. It is not known whether it is the result of a downregulation by the fungus itself, and therefore a part of its interaction mechanism, or if it is the result of actions of the competitor's effectors (28).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the case of the interaction between P. coccineus and C. puteana, our data are convergent with these findings (609 overexpressed and 734 underexpressed), but for the interaction with B. cinerea, our results are divergent, with the number of underexpressed transcripts almost 7 times higher than the number of overexpressed transcripts. Multiple studies have reported that interspecific fungal interactions lead to genetic repression (11,(26)(27)(28), but the cause of this regulation is unclear. It is not known whether it is the result of a downregulation by the fungus itself, and therefore a part of its interaction mechanism, or if it is the result of actions of the competitor's effectors (28).…”
Section: Discussionmentioning
confidence: 99%
“…Current knowledge also indicates that during an interaction, fungi produce and secrete enzymatic effectors, including metalloproteins (12,57) and secondary metabolites (1), in order to interfere with their competitors. Interacting fungi also have to repair the structures damaged during the interaction, such as cell walls (28) or DNA (11). Setting up these attack and defense pathways has a metabolic cost, which is another factor that explains the growth limitation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Differential display is now being applied in the biological control field. It recently allowed the identification of an aspartyl protease from Trichoderma asperellum (45) and genes differentially expressed during nonself fungal-fungal interactions of the decomposing basidiomycete Physisporinus sanguinoletus (22). Compared with differential display, cDNA-amplified fragment length polymorphism (cDNA-AFLP) analysis (5), a nonbiased technique based on PCR amplification, offers the advantage of higher reproducibility (16).…”
mentioning
confidence: 99%